A treatment for the fiscal deficit : taxation of customer loyalty programmes in the retail pharmaceutical industry - Coetzee, E.S.M. (Liza) (University of Pretoria, 2023)
Mini Dissertation (MCom (Taxation))--University of Pretoria, 2022.